2015
DOI: 10.1007/s10973-015-4984-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic stability of darunavir and its formulation

Abstract: Darunavir (DAR) is a synthetic antiretroviral drug widely used around the world as an important component of HIV therapy. Usually, DAR is commercialized at ethanolate crystalline form. Under different environmental conditions, different pseudo-polymorphic forms arise and convert each other. The importance of the drug stability control is to ensure their quality, efficacy and safety. Therefore, the aim with this work was to evaluate the solidstate stability of DAR under stressed conditions and assess the role p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the light of these considerations, there are several factors affecting the dissolution properties from pharmaceutical dosages, which include the solid-state polymorphism (Snider, Addicks, Owens, 2004;Corrêa et al, 2016). The pharmaceutical industry manufactures solid dosage forms of ROSC using the amorphous solid, which has been reported as a solid-state form that shows satisfactory stability and low tendency to crystallize.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of these considerations, there are several factors affecting the dissolution properties from pharmaceutical dosages, which include the solid-state polymorphism (Snider, Addicks, Owens, 2004;Corrêa et al, 2016). The pharmaceutical industry manufactures solid dosage forms of ROSC using the amorphous solid, which has been reported as a solid-state form that shows satisfactory stability and low tendency to crystallize.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that pharmaceutical compounds such as cephalexin, chloramphenicol, digoxin, spironolactone, sulfathiazole, carbamazepine and retroviral agents [ 9 , 10 , 11 , 12 ] undergo transitions during drying processes, spraying, grinding, compression, excipient addition and the preparation of tableting. Polymorphism in pharmaceutical solids can be a critical manufacturing variable and therefore has to be investigated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%